WANITA DAN ILMU PENGETAHUAN PADA ZAMAN RASULULLAH: TELAAH LITERASI DAN PENDIDIKAN DALAM PERSPEKTIF HADIS - Novia Lisliningsih; Salmi Wati (Adisam Publisher, 2025)
This research is based on the premise that education was not limited to men alone during the time of Rasulullah SAW; women were also prioritized in education and literacy. Referring to relevant hadiths, this article examines the literacy and education of women in the era of Rasulullah SAW. The purpose of this study is to explore the role of women in knowledge during the early Islamic period and how these teachings influence our perspectives on women’s education today. This study employs a qualitative approach through literature and hadith analysis. The findings reveal that Islam provides a strong foundation for women's education from the very beginning. The results of this research also reinforce Islam's contribution in elevating the status of women and providing opportunities for them to enhance their capacities in education.